ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGANGGURAN PEREMPUAN - Ida Ayu Nyoman Saskara; David Kaluge (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2009)
The aim of this is to analyses women unemployment based on Indonesia Provinceusing inflation, investment, women involvement at labor market, and also meninvolvement at labor market as independent varaibles.The panel data is used from26 provinces in Indonesia for 5 years (2002-2006), using double log regression. Theresult shows that employing women have negative effect and significant, whileemploying men has positive effect and significant to the women employment. Inflationand investment have positive and negative effect but insignificant.Keywords: inflation, investment, women unemployment and labor market